PENINGKATAN PEMAHAMAN PEMBAGIAN HAK MEWARISI BAGI GENERASI MUDA DI KELURAHAN LIBUO KABUPATEN POHUWATO - Abdussamad, Zamroni; Puluhulawa, Irlan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The division of inheritance that is not in accordance with the amount and object of inheritance in accordance with inheritance law is also caused by the heirs, who in fact are the younger generation, not knowing the inheritance distribution mechanism in accordance with the actual inheritance law system. Therefore, this service is carried out in the form of an initial survey of inheritance rights issues for youth groups, legal counseling on the distribution of inheritance rights for the younger generation, and the making of an easy-to-use and easy-to-understand inheritance division pocket book with current models and language. The results of the service by hacking a product in the form of a pocket book for the community in general and the younger generation in particular in Buhu Jaya village provide benefits for the village with the understanding possessed by the younger generation of inheritance rights, it will create a community environment that is far from disputes and creates a sense of security and comfort among fellow community members.